Analisis Dampak Kepemimpinan Transaksional Dan Transformasional Terhadap Pembelajaran Organisasi Pada Pt Bangun Satya Wacana Surabaya - Irra Chrisyanti Dewi; Nuri Herachwati (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2010)
This study links the important field of management research empirically, namely the various scope theory of leadership and organizational learning process. Specifically, this study discusses three things: 1) the impact of transactional leadership, and 2) transformational leadership on organizational learning processes, and 3) whether the influence of transformational leadership is stronger than transactional leadership. The results show that transactional leadership is more powerful in explaining variation and change of employee behavior toward organizations learning, compared with transformational leadership. Ability of transactional leadership style explain variations of organizational learning and change by 10.2%, whereas the ability of transformational leadership style explain variations of organizational learning and change of 5.9%. These findings depict an exchange-based approach to leadership and employee needs to do the job, it will be better to create the employee to make the learning process both in the process of information acquisition, information distribution, information interpretation, and creating changes in behavior and knowledge of employees.